Behavioral Inhibition Underlies the Link Between Interoceptive Sensitivity and Anxiety-Related Temperamental Traits - Lyyra, Pessi; Parviainen, Tiina (Frontiers in Psychology, 2018)
Interoceptive sensitivity is a biologically determined, constitutional trait of an individual. High interoceptive sensitivity has been often associated with proneness to anxiety. This association has been explained by elevated autonomic responsiveness in anxious individuals. However, in a heartbeat discrimination task (discrimination of heartbeats’ simultaneity to an external stimulus) low cardiac responsiveness has accompanied enhanced performance. The relation between these factors seems task dependent, and cannot comprehensively explain the link between interoceptive sensitivity and anxiety. We explored for additional explanatory factors for this link. More specifically, we studied which anxiety-related temperamental traits most strongly predict interoceptive sensitivity in the discrimination task. Compatibly with earlier findings, interoceptive sensitivity was positively associated with individual trait anxiety and also other related traits such as negative affect, emotional intensity, and introversion. Interestingly, behavioral inhibition was the temperamental trait that most strongly predicted high interoceptive sensitivity, and, in fact, accounted for its significant associations with the other anxiety-related temperamental traits. Good performance on heartbeat discrimination task may reflect adaptive attentional control abilities in behaviorally inhibited individuals. These results can improve our understanding of how interoceptive sensitivity and other traits together determine the personality and wellbeing of a human individual.